Gala du Jeune Ballet de France - Taglioni, Marie 1804-1884; Deldevez, Édouard Marie Ernest 1817-1897; Pugni, Cesare 1802-1870; Nascimento, Mílton 1942-; Ferran, José; Adam, Adolphe 1803-1856 (8 Productions, 1997)
Founded in 1983 by Robert Berthier, the Jeune Ballet de France used to have a very special place in the ballet tradition in France. Hiring some of the youngest and most promising dancers after the conservatories, it was a perfect way to fly towards a bright carreer. The JBF repertoire is particularly eclectic, ranging from the greatest classical ballets to more contemporanean works. The many tours of the company helped the choreographic art to be broadcast. In this programme, filmed at the Opéra Théâtre de Massy in 1997, we can admire famous excerpts from Paquita, Le Corsaire, Le Papillon ... The dancers displayed here have now earned international fame: this is a unique opportunity to watch them at the beginning of their carreers. You will most notably see the Cuban dancer Joan Boada (who then entered the San Francisco Ballet), Yukari Kami (hired in 1997 at the Ballet du Grand Théâtre de Genève), Boyd Laud (today a principal dancer at the Opéra national du Rhin), Amilcar Moret (Ballet de Hambourg), Guennadi Nedviguine (San Francisco Ballet), among others
Keywords: Ballets; Ballets -- Excerpts; Internet videos